Keberagamaan Koruptor Menurut Psikologi (Tinjauan Orientasi Keagamaan dan Psikografi Agama) - Roni Ismail (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
All of religion forbids all followers to do something that could harm others.  Any religion has principles that must be complied with by all adherents, either ban or printah. One of the ban as "stealing money" corruption. This Coruption is certainly very forbidden by any religion, because Coruption not only harms the individual and the group, but much more dangerous is the people. Many of the perpetrators of corrupt framing comply with such personality that embraced religion. Is it true that someone who actually obey the religion he embraced still violate religious rules? Aartikel will analyze religious corruption from the perspective of psychology of religion that would be obtained by using the empirical explanation of the two theories in the psychology of religion, namely: Religious Orientation and Religion or psychographic dimensions Religiosity. Evident in a corrupt personality split (split personality) as opposed to monotheism. People who have split personality is not one word and deed, while the tauhid one word and deedwhat is believed, it is said, thought the same as what it does.